From Rastra to BPNT: An Empirical Quantitative Evaluation of Food Assistance Reform in Indonesia - Sofa, Wahyuni Andriana (Economics and Finance in Indonesia, 2023)
Since 2017, Indonesia has shifted from its Rastra program to BPNT, an e-voucher food-based initiative, due to issues with targeting and effectiveness in social assistance. This paper examines the impact of this transition on poverty alleviation and food security, using SUSENAS 2018 and propensity score matching. Findings indicate BPNT is less effective than Rastra in reducing households’ poverty risk and has led to decreased food access and nutrition. Impact variations are noted, which are found to be worse in households with less-educated heads, located in Java Island, and rural areas.